Phytochemical Profile and Antibacterial Activity of Nigella Sativa against Biofilm-producing Bacteria Uropathogens - Abaka, AbdulAzeez Mumsiri; Dahiru, Mubarak Muhammad; Abubakar, Keta Biman; Luka, Jordana; Abubakar, Aisha; Abdullahi, Tukur Baba; Barau, Saminu Hamman (Biology, Medicine, & Natural Product Chemistry, 2024)
This study explores the antibacterial effects of Nigella sativa seeds on bacteria obtained from clinical samples. The aim was to assess the antibacterial properties of both aqueous and methanolic extracts of Nigella sativa seeds against E. coli, S. aureus, and P. aeruginosa. The three samples were collected from the Microbiology Laboratory of Modibbo Adamawa Medical Centre and were reconfirmed using culture, microscopy, and some biochemical tests. The seed samples of N. sativa were procured from herbal point Yola, Adamawa State, Nigeria. The phytochemical assay of the extracts revealed the presence of flavonoids, alkaloids, tannins, phenols, cardiac glycosides, steroids, saponins, and terpenoids in both extracts. The highest antibacterial activity against S. aureus, E. coli, and P. aeruginosa was demonstrated by the aqueous extract of N. sativa seeds, with inhibition zone diameters of 19.30 ±0.61 mm, 8.10 ±2.17 mm, and 12.00 ±0.29 mm, respectively. However, the methanol extract exhibited slightly greater activity against E. coli and P. aeruginosa, with inhibition zone diameters of 12.10 ±0.38 mm and 13.80 ±0.40 mm, respectively. Both methanol and aqueous extracts showed minimum inhibitory concentrations (MICs) of 25 mg/mL against S. aureus and E. coli. Similarly, for P. aeruginosa, the MIC was 25 mg/mL for methanol extract and 50 mg/mL for aqueous extract. The minimum bactericidal concentration (MBC) for both extracts against S. aureus and E. coli was determined to be 25 mg/mL. However, for P. aeruginosa, the MBC was 25 mg/mL for the aqueous extract and 50 mg/mL for the methanol extract. The study indicates that N. sativa seed extract possesses antibacterial properties against S. aureus and P. aeruginosa, underscoring its potential as an effective medicinal antibacterial agent.